Le site antique de la clinique des Dames Blanches à Tours (Indre-et-Loire) : aménagements d’un embarcadère romain sur la Loire et évolution du trait de rive - Nicolas Fouillet; Philippe Gardère (Gallia)
During the Early Roman Empire period the site of “clinique des Dames Blanches” in Tours/Caesarodunum (Indre-et-Loire) was located a few dozen metres from the Loire river, along the river bank road which lead to the ancient city of Tours/Caesarodunum. This road corresponds to the current street, rue Courteline. A portion of this Roman axis, probably established in the first half of the 1st c. AD, could be investigated at the limit of the explored area. The excavation made it possible to uncover a Roman landing stage 8 m wide, probably connected to the riverbank road. The development is marked by a multitude of oak piles deeply driven into the alluvial deposits. Stratigraphic and dendrochronological analyses show that four different phases of the landing stage followed one another in the same place between the mid-1st and the 2nd c. AD. The transformations are carried out according to the rhythms of the river: refilling or reconstructions in front of the initial structures. The fourth state of the pier contrasts strongly with the preceding three, as it no longer corresponds to a simple access ramp to the river. Indeed, the landing stage of the 2nd c. AD, as well as its surroundings, is reinforced by a complex assemblage of wooden caissons measuring 8 m on each side, arranged in a checkerboard pattern. Each module is backfilled with drainage materials, mainly Loire sand. This wooden infrastructure was intended to reinforce the bank and to limit erosion, which is a particular problem in a riverbank context. The move to a caisson construction could thus indicate an intensification of the erosive activity of the Loire river, as well as a change in the status or importance of the access structure to the river. The installation underwent no further major redevelopment before being definitively silted up and abandoned between the 2nd c. and the 4th c. AD. During the Late Roman Imperial period a slowing down of the sedimentartion provided a usable space on the flood plain. The occupation of the riverbank then resumed in the form of a suburban sepulchral area established along the Roman road. The funerary complex included at least 23 individuals: men, women and children of all ages, without any particular spatial distribution. Most of the burials are dated to the Late Roman Imperial period (4th c. AD), according to the grave goods furnishings and radiocarbon dating. From this period on the channel was gradually filled in, but the study area was still subject to the river floods, as shown by the large-scale sedimentary ablation that obliterated the Roman tombs. After this poorly dated episode (between the mid-4th c. and the 9th c. AD), the sedimentological evolution attests to the distance of the main course of the river towards the north, making it possible once again to occupy the central zone of the site. A new riverbank road was built at the very moment when the floods stopped regularly invading the site. A settlement dating back to the 9th-12th c. AD developed between the two roads.